2020
DOI: 10.7784/rbtur.v14i1.1599
|View full text |Cite
|
Sign up to set email alerts
|

A viagem que mais contribuiu para quem eu sou: explorando as dimensões da Experiência Turística Eudaimônica

Abstract: Com base em uma revisão do conceito de eudaimonia, o estudo propõe uma definição para o constructo experiência turística eudaimônica e identifica 15 potenciais dimensões constituintes do constructo, a partir de uma extensa revisão da literatura nos domínios da psicologia positiva, psicologia existencial-humanista, psicologia do desenvolvimento (estudos sobre a formação da identidade na linha Eriksoniana) e do turismo (estudos sobre experiência turística transformadora). Com o objeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
2
0
1
Order By: Relevance
“…Tercer tema: Beneficios de la ET en el visitante, a) un interesante estudio enmarcado en la Psicología positiva, proponiendo a la experiencia turística como facilitador del crecimiento interior. Analiza la ET eudaimónica desde una perspectiva innovadora (Medeiros et al, 2020); y b) un estudio que analiza el impacto espiritual del turismo religioso en la ET, considerando que el visitante se beneficia de la transformación espiritual mediante la ET centrada en la religiosidad ( Álvarez y Aulet, 2021). Ambos estudios ejemplifican el aporte que otras ciencias pueden realizar en este campo, donde la psicología, sociología, antropología, etc., amplían nuestro conocimiento de las diversas facetas de la ET en la vida de las personas.…”
Section: Resultsunclassified
“…Tercer tema: Beneficios de la ET en el visitante, a) un interesante estudio enmarcado en la Psicología positiva, proponiendo a la experiencia turística como facilitador del crecimiento interior. Analiza la ET eudaimónica desde una perspectiva innovadora (Medeiros et al, 2020); y b) un estudio que analiza el impacto espiritual del turismo religioso en la ET, considerando que el visitante se beneficia de la transformación espiritual mediante la ET centrada en la religiosidad ( Álvarez y Aulet, 2021). Ambos estudios ejemplifican el aporte que otras ciencias pueden realizar en este campo, donde la psicología, sociología, antropología, etc., amplían nuestro conocimiento de las diversas facetas de la ET en la vida de las personas.…”
Section: Resultsunclassified
“…TT contributes to both hedonic and eudaimonic experiences [63], yet as its nature thrives in the discovery of self, personal growth, and construction of identity, it aligns more with the eudaimonic experiences [64]. In their research on the meaning of transformative tourism and its facilitators and inhibitors, Pung and Del Chiappa (2020) observed that while discussing the long-lasting effects of their transformation, participants reported experiencing eudaimonic well-being, rather than a hedonic one, transformation becoming one of the main elements in eudaimonic experiences [25].…”
Section: Eudaimonic Experiencesmentioning
confidence: 99%
“…For example, in visiting friends and relatives (VFR) tourism (Backer, 2019), physical contact with family or friends, or the love for the physical features of the destination (i.e., connection with nature) could be important to psychological wellbeing independent of whether this form of tourism may be perceived as meaningful, or whether it creates negative emotions (such as sadness) or positive emotions (like joy). With some notable exceptions, however (Laing & Frost, 2017; McCabe & Johnson, 2013; Medeiros et al, 2020), the role of relationships (both social connections and connection with nature), is typically not assessed in studies which measure tourist wellbeing.…”
Section: Interpreting Wellbeingmentioning
confidence: 99%